2020
DOI: 10.3390/biomedicines8030064
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Anti-Inflammatory Activity of Plant Polyphenols

Abstract: Inflammation is considered the first physiological response of the human body to infection or injury, playing a critical role in both innate and adaptive immunity [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Immuno-stimulation induced by AFB1 increases the synthesis of inflammatory markers and free radicals, which lead to chronic inflammation and cancer [ 42 , 43 ]. Anti-inflammatory activities of plant bioactive compounds have been reported in acute and chronic inflammation in animal models [ 44 , 45 ], and recent data have shown that they can be used for counteracting the toxic effect of AFB1 [ 24 , 46 , 47 ]. Our previous results have shown that GSM addition into AFB1-contaminated diet induced the amelioration of liver injuries and decreased inflammation and oxidative stress in the liver of intoxicated piglets by decreasing the MAPKs and NF-κB signaling pathways overexpressed by the AFB1 diet [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immuno-stimulation induced by AFB1 increases the synthesis of inflammatory markers and free radicals, which lead to chronic inflammation and cancer [ 42 , 43 ]. Anti-inflammatory activities of plant bioactive compounds have been reported in acute and chronic inflammation in animal models [ 44 , 45 ], and recent data have shown that they can be used for counteracting the toxic effect of AFB1 [ 24 , 46 , 47 ]. Our previous results have shown that GSM addition into AFB1-contaminated diet induced the amelioration of liver injuries and decreased inflammation and oxidative stress in the liver of intoxicated piglets by decreasing the MAPKs and NF-κB signaling pathways overexpressed by the AFB1 diet [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…exhibit anti-inflammatory activity through different mechanisms, including the impairment of the nuclear factor-kB pathway, inhibition of C-reactive protein, and modulation of proinflammatory mediators. [36][37] The beneficial or harmful effects of polyphenols on pregnancy are contradictory. In this regard, a recent review shows that a high concentration of polyphenols in diet may negatively affect the development of the fetus and the offspring's health.…”
Section: Discussionmentioning
confidence: 99%
“…As well as featuring oil-rich fish, healthy dietary patterns such as Mediterranean-style diets and a dietary pattern that corresponds to the Eatwell Guide in the UK tend to be plant-based, consisting of high amounts of fibre-rich foods providing a variety of fibre types (such as wholegrains and pulses), which are important for gut health (Lockyer & Stanner 2019;Lockyer & Spiro 2020). Healthy dietary patterns additionally contain plenty of fruit and vegetables, which also provide fibre alongside a range of micronutrients and plant-specific compounds such as polyphenols, which have been suggested to have immune regulatory and anti-inflammatory effects (Sangiovanni & Dell'Agli 2020). Though several mechanisms have been suggested for polyphenols, a key mechanism proposed is that these compounds interfere with the nuclear factor jB (NF-jB) pathway, which ordinarily promotes the expression of adhesion molecules, cytokines and other pro-inflammatory mediators (Yahfoufi et al 2018).…”
Section: Healthy Dietary Patternsmentioning
confidence: 99%